Model Pemberdayaan Masyarakat di Wilayah Pesisir dalam Menanggulangi Kemiskinan di Kabupaten Buton, Sulawesi Tenggara - Rahim, Manat; Tahir, Madjiani; Rumbia, Waly Aya (Journal the Winners: Economics, Business, Management, and Information System Journal, 2014)
Poverty is a social reality characterized by underdevelopment in the social, economic, cultural, political, educational and natural factors that directly influence the inability of society, so as to be poor. The effort to reduce poverty is done by getting the community development approach through government programs i.e. PNPM-MP and strengthening unit districts management institutions. The data used were primary data obtained from the field survey with a list of questions; samples were 98 respondents. Research analysis used descriptive quantitative method and community empowerment model approach. Research shows that the family economic empowering 10 from 12 respondents or 83.33% increased in family income and did not work for 16,67% respondents. Meanwhile, the traditional farmer empowerment productive effort 36 form 46 respondents or 78,26% succeeded to increase household income of farmers and 21,74% were not able to increase the income of farm households. Meanwhile, venture capital empowerment fishermen increased fishing activity and managed marine products with a success rate of 55% and 45% did not succeed.